VD_FINDINFO AP / 2011 / 68 vom 20. Dezember 2010 - VD Tribunal cantonal (2010)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT | 187 CP, 411 let. h CPP, 411 let. i CPP, 411 let. j CPP, 414a CPP, 418a CPP, 447 CPP, 448 al. 3 CPP